How Cloud Computing can help SMEs to grow faster? - Hasan, Ahmed Anwar (2010)
In recent years, Cloud computing has successfully created hype and lots of people think that cloud computing might be the next big thing. The cloud platform is growing rapidly and lots of cloud service provider companies are coming up with huge number of innovative ideas where they are addressing specific needs of different organisations. The cloud computing is based on a service model architecture which is highly customisable and can fit into a specific or unique business process. Cloud computing saves time, labor, cost, and enhance the performance of business process. Hence, SMEs who are highly cost conscious and suffer from lack of human resources, can be greatly benefited from cloud computing. However, there are some disadvantages of cloud computing as well. In this report, an effort has been made to understand and analyse what factors affect the growth of SMEs and how cloud computing can help to increase the efficiency of those factors thus help SMEs to grow faster in this competitive business environment. In my research, I analysed the merits, demerits, risk factors and risk mitigation factors of cloud computing to understand whether it can embraced by the SMEs and ended up with the idea that today or tomorrow companies have to use cloud computing to operate successfully in this competitive global business environment.